STURGE-WEBER SYNDROME IN AN EPILEPTIC CHILD: A CASE REPORT - Christofer Sathya Wijaya Budi Sarwono (Berkala Ilmiah Kedokteran Duta Wacana, 2021)
Sturge Weber Syndrome (SWS) is a congenital neurocutaneous disorder with a facial capillary malformation Port-wine stains (PWS), abnormal blood vessels of the brain (leptomeningeal angioma), or abnormal blood vessels in the eye predisposing to glaucoma. The incidence of Sturge Weber Syndrome (SWS) is a rare entity that accounts about 3 of 1000 births with PWS, 5% of them suffer SWS. We report a case of 5-years-old girl who presented with a three-days history of muscle weakness of right upper and lower limb followed by headache, loss of consciousness, dizziness, with history of hemangioma facial without any symptoms like fever, nausea, vomit, and dysarthria. Patient was a refferal patient from Sarila Husada Hospital Sragen. Head CT-Scan was performed on the admission day on Sarila Husada Hospital Sragen and confirmed by Bethesda Hospital Radiologist revealed a subcortical calcification at frontal lobe and parietal sinistra with mild atrophy at bifrontalis lobes that support SWS.